Clinical impact of novel cardiovascular magnetic resonance technology on patients with congenital heart disease: a scientific statement of the Association for European Pediatric and Congenital Cardiology and the European Association of Cardiovascular Imaging of the European Society of Cardiology. - Voges, Inga; Raimondi, Francesca; McMahon, Colin J.; Ait-Ali, Lamia; Babu-Narayan, Sonya V.; Botnar, René M.; Burkhardt, Barbara; Gabbert, Dominik D.; Grosse-Wortmann, Lars; Hasan, Hosan; Hansmann, Georg; Helbing, Willem A.; et al. (European Heart Journal - Cardiovascular Imaging, 2024)
Cardiovascular magnetic resonance (CMR) imaging is recommended in patients with congenital heart disease (CHD) in clinical practice guidelines as the imaging standard for a large variety of diseases. As CMR is evolving, novel techniques are becoming available. Some of them are already used clinically, whereas others still need further evaluation. In this statement, the authors give an overview of relevant new CMR techniques for the assessment of CHD. Studies with reference values for these new techniques are listed in the Supplementary data online, supplement.
EVALuna2:586093